Religion and migration : exploring the religious identities of young migrants in Ireland and young people with migration background in Germany - Kmec, Vladimir (Irish School of Ecumenics, 2015)
This dissertation explores the formation of religious identities of young Christian migrants in Ireland and young Muslim people with migration background in Germany. The objective of the dissertation is to investigate patterns of religious identity formation in relation to young people’s migration experience and background which prompt and facilitate a change of religious identities. Accordingly, the research analyses factors that contribute to the formation of religious identities of migrants and people with migration background. Finally, the aim of the research is to understand what role religion plays and how it functions for these young people. To this purpose, the research focuses on a broader dimension of identity construction - not only how immigrant religious communities impact on young people’s religious identities but how their identities are shaped within their everyday context. In other words, the work explores how young Christians and Muslims perceive, understand and express their religious identity in their everyday situations.
Embargo End Date: 2022-01-01
Keywords: Religions, Theology & Ecumenics Ph.D.; Ph.D. Trinity College Dublin, 2015